Analisis Yuridis Terhadap Keterlambatan Pemberitahuan Pengambilalihan Saham (Akuisisi) (Studi Putusan KPPU Nomor 31/Kppu-M/2020) - Huda, Asrul; Santoso, Budi (Notarius, 2023)
AbstractIn the case of KPPU's Decision Number 31/KPPU-M/2020, according to KPPU, there was a delay in notification of the takeover of PT Tanjung Kreasi Parquet Industry shares by PT Dharma Satya Nusantara, Tbk. This study aims to examine the regulation of the obligation to notify the takeover of shares in the perspective of business competition law and to analyze whether the KPPU's decision Number 31/KPPU-M/2020 is in accordance with the provisions of Law No. 5 of 1999 and PP No. 57 of 2010. The research method in this study is the method normative juridical. The results of this study indicate that there is an obligation to give written notification to KPPU on the acquisition of shares with the aset value and/or sales value exceeding a certain amount no later than 30 (thirty) days from the date of the takeover. The sanction for late notification of share acquisition by PT Dharma Satya Nusantara, Tbk has complied with the provisions of Law No. 5 of 1999 and PP No. 57 of 2010.Keywords: notification; acquisition; kppuAbstrakKasus Putusan KPPU Nomor 31/KPPU-M/2020, menurut KPPU terjadi keterlambatan pemberitahuan pengambilalihan saham PT. Tanjung Kreasi Parquet Industry oleh PT. Dharma Satya Nusantara, Tbk. Penelitian ini bertujuan mengkaji pengaturan kewajiban pemberitahuan pengambilalihan saham dalam perspektif hukum persaingan usaha dan menganalisis apakah putusan KPPU Nomor 31/KPPU-M/2020 telah sesuai dengan ketentuan UU No. 5 Tahun 1999 dan PP No. 57 Tahun 2010. Metode penelitian dalam penelitian ini adalah metode yuridis normatif. Hasil penelitian ini diketahui adanya“kewajiban pemberitahuan secara tertulis kepada KPPU atas pengambilalihan saham dengan nilai aset dan/atau nilai penjualannya melebihi jumlah tertentu paling lama 30 (tiga puluh) hari sejak tanggal pengambilalihan tersebut. Sanksi keterlambatan pemberitahuan akuisisi saham yang dilakukan oleh PT. Dharma Satya Nusantara, Tbk telah sesuai dengan ketentuan UU No. 5 Tahun 1999 dan PP No. 57 Tahun 2010.Kata kunci: notifikasi; akuisisi; kppu